PENGARUH KELEMBABAN TERHADAP INTENSITAS SERANGAN, AKTIVITAS MAKAN DAN DAYA HIDUP CRYPTOTERMES CYNOCEPHALUS LIGHT. - Ginuk Sumami (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A preliminary study on the effect of air humidity to infestation intensity, feeding activity and survival of the dry- wood termite Cryptotermes cynocephalus Light, has been conducted by using flue levels of humidity i.e 37.75%; 70.21%; 83.38%; 87.75% and 97.0%.The salts CaCl2, NaCl, KCl and K2S04 were respectively used to control the air humidity of 37.73% to 87.75%; whereas H20 was used to control the air humidity of 97.0%. Rubber wood samples of 1.5 cm by 2.5 cm by 5.0 cm with a hole of 3 cm by 1 cm were prepared to feed the termite workers. The results reveal that the lowest feeding activity, infestation intensity and survival of the dry-wood termite were indicated by the 37.73% air humidity; where as the highest feeding activity and survival of the termite were indicated by the 90% air humidity. Meanwhile there were no significant influence of infestation intensity within the air humidity of more than 70%.